Evaluation of Stucture Performance the Building a Regional Police Headquarters of Lampung using Direct Displacement Based Design Method of Base Shear Forces - Hilmi, Zihan Ramdan; Bayzoni, Bayzoni; Husni, Hasti Riakara (Universitas Lampung, 2020)
Direct Displacement Based Design (DDBD) is a new method in computing the loading of earthquakes resistant building structures with displacement as a performance target, which is considered to be more efficient than the method often used previously, namely the Force Based Design (FBD). The purpose of this research is evaluate the performance of the Lampung Regional Police Headquarters building based on the ATC-40 and FEMA 440, where the dimensions of the structure used from shop drawings and can be change if the dimensions not meet requirements. The loads used are gravity loads and base shear force designed using DDBD, where the design performance target is life safety. In the evaluation process of this research, there is one type of main beam that must be changes in dimensions, and the result of structure performance evaluation is immediate occupancy, based on ATC-40 and FEMA 440. Keywords: Displacement, DDBD, Evaluation of Performance.